INOVASI KURIKULUM BERBASIS FUNGSI MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN - Amelia putri utami; Tri Agustinawati; Dewi Etika Syari; Mohamad Muspawi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2026)
This study aims to examine curriculum innovation and the role of curriculum management in improving the quality of education. The method used is qualitative research with a literature study approach, through data collection from journals, books, and other relevant scientific sources. The results of the study indicate that curriculum innovation is a planned renewal to improve the education system to suit the latest developments and community needs. Effective curriculum management through management functions, namely planning, organizing, implementing, and supervising (POAC), plays a crucial role in improving the quality of learning. In addition, the quality of education is influenced by several key factors such as principal leadership, teacher competence, student engagement, a dynamic curriculum, and collaboration with various parties. Thus, curriculum innovation supported by good management can be the key to improving the quality of education sustainably.